The influence of lubricating oil on deposits formation in a diesel engine under the operation condition of high power density. (28th January 2013) - Dong, Lihui; Liang, Xingyu; Shu, Gequn
ABSTRACT: The requirements of higher power density and stricter regulations on emissions of internal combustion engines lead to lubricating oil's role shifting from simply lubricating to adapting higher power density and to achieving lower emissions. An important factor influencing an engine's power and emissions is the deposits in the engine. Lubricating oil is a chief contributor to deposits formation. The objective of this paper is to investigate the influence of lubricating oil on deposits formation when the engine is operated under high power density. Metal elements content in lubricating oil and changes to power and emissions were measured to verify deposits changes. Different power densities can be achieved by adjusting the fuel supply system in the engine. Three kinds of synthesised lubricating oils were used in the investigation. The temperature of the oil pan and cooling water was strictly controlled. The experimental results demonstrated well the influence of the quality of different kinds of oil on deposits formation. Copyright © 2013 John Wiley & Sons, Ltd.